Detection of minor flavonoids from Tragia plukenetii A. R. Smith - Narwade, V T; Waghmare, A A; Vaidya, A L (International Multidisciplinary Research Journal, 2012)
The minor flavonoids from Tragia plukenetii A. R. Smith were extracted by using different solvent and they were identified and detected by Paper Chromatography (PC) and spectroscopic method. The minor flavonoids classes like chalcones, aurones and flavanones were detected from T. plukenetii A. R. Smith.